2014
DOI: 10.1186/2042-6410-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-biased chromatin and regulatory cross-talk between sex chromosomes, autosomes, and mitochondria

Abstract: Several autoimmune and neurological diseases exhibit a sex bias, but discerning the causes and mechanisms of these biases has been challenging. Sex differences begin to manifest themselves in early embryonic development, and gonadal differentiation further bifurcates the male and female phenotypes. Even at this early stage, however, there is evidence that males and females respond to environmental stimuli differently, and the divergent phenotypic responses may have consequences later in life. The effect of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 114 publications
1
28
0
1
Order By: Relevance
“…The long arm of murine ChrY encodes several multicopy gene families, which exhibit significant strain-specific copy number variation (CNV), and the physiological roles of which are only beginning to be understood (20,21). Importantly, our studies in EAE and CVB3-induced autoimmune myocarditis revealed a strong association between CNV in multicopy ChrY genes and susceptibility to these autoimmune diseases (27,46).…”
Section: Copy Number Variation In Chry Multicopy Genes Does Not Corrementioning
confidence: 87%
See 1 more Smart Citation
“…The long arm of murine ChrY encodes several multicopy gene families, which exhibit significant strain-specific copy number variation (CNV), and the physiological roles of which are only beginning to be understood (20,21). Importantly, our studies in EAE and CVB3-induced autoimmune myocarditis revealed a strong association between CNV in multicopy ChrY genes and susceptibility to these autoimmune diseases (27,46).…”
Section: Copy Number Variation In Chry Multicopy Genes Does Not Corrementioning
confidence: 87%
“…Importantly, these data suggest that nonendocrine cell-intrinsic (genetic) sex-specific factors may contribute to disease susceptibility in males. In this regard, the concept that genes on the X and Y chromosomes (ChrX and ChrY) may influence sex differences is being increasingly recognized (18)(19)(20)(21), and it was recently suggested that the widely expressed ancestral singlecopy ChrY genes may function as dosage-sensitive regulators of gene expression, translation, and protein stability, and as such may play essential roles in male viability, development, and sex differences in health and disease (22).…”
mentioning
confidence: 99%
“…While the basis for this sex difference is unclear, it is consistent with recent findings that exposure to the persistent organic pollutant polychlorinated biphenyls (PCB) decreased Bdnf (but not Grin2b ) protein levels and Bdnf -mediated signaling in the adult male rat cerebral cortex [43]. We previously observed a male-specific effect of prenatal BPA exposure on reductions in hippocampal Bdnf and Grin2b gene expression and cognitive performance, and these sexspecific effects were likely the typical response to prenatal adversity [20] and may have been mediated by chromosomal, hormonal and epigenetic differences between males and females during fetal development [4446]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mitochondrial function varies in adult males and females but the origin of these differences is unknown. [116,117] Acknowledging these gaps should lend strong impetus for bridging them with detailed, mechanistic studies.…”
Section: Caveats and Opportunitiesmentioning
confidence: 99%